2006
DOI: 10.1682/jrrd.2005.04.0078
|View full text |Cite
|
Sign up to set email alerts
|

Pressure changes under the ischial tuberosities of seated individuals during sacral nerve root stimulation

Abstract: Abstract-Neuromuscular stimulation via the sacral nerve roots is proposed for prevention of ischial pressure ulcers following a spinal cord injury (SCI). Acute effects of sacral functional magnetic stimulation (FMS) on seat interface pressure changes were investigated in five nondisabled volunteers. Similar effects were demonstrated with functional electrical stimulation in people with SCI who used a sacral anterior root stimulator implant. The results indicated that sacral nerve root stimulation, either by FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
0
27
2
Order By: Relevance
“…Recently, we used FMS to investigate the dynamic effects of sacral nerve root stimulation on ischial pressure changes in nondisabled people. Our results demonstrated that ischial pressure significantly decreased during optimal stimulation [23]. However, we reported neither the effects of FMS on people with SCI nor the tissue hemodynamic changes during FMS.…”
Section: Introductioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Recently, we used FMS to investigate the dynamic effects of sacral nerve root stimulation on ischial pressure changes in nondisabled people. Our results demonstrated that ischial pressure significantly decreased during optimal stimulation [23]. However, we reported neither the effects of FMS on people with SCI nor the tissue hemodynamic changes during FMS.…”
Section: Introductioncontrasting
confidence: 64%
“…During optimal magnetic stimulation in the noninvasive magnetic stimulation study, maximum effects were obtained at the approximately S2 foramen level in all five subjects with SCI, which corresponds to a study on FMS in nondisabled people [23]. With electrical stimulation through the SARS implant, maximum reduction in peak pressure was obtained when the S2 nerve was stimulated with a pulse width between 64 and 600 μs, a frequency of 20 pps, and an amplitude of "1.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…1,4 In selected patients, sacral deafferentation without implantation of an anterior root stimulator has been proven to be clinically useful as well. 5 If patients decide to undergo rhizotomy without receiving a stimulator, bowel evacuation and erectile function may become a problem, as reflex activity can be impaired by surgery.…”
Section: Discussionmentioning
confidence: 99%